A panel fsQCA investigation on European regional innovation - David Pickernell (Technological Forecasting and Social Change, 2024)
Taking an evolutionary economic geography perspective, we build on literature on innovation modes, the aim of this study being to explain variations in SME innovation performance across European regions over time. Drawing on five waves of data from the EU Regional Innovation Scoreboard between 2011 and 2019, our sample includes 221 regions across 27 EU Member States, as well as Norway, UK, Serbia, and Switzerland. We apply nascent panel fuzzy-set Qualitative Comparative Analysis to explore how different combinations of SME innovation modes explain innovation performance across different EU regions (i.e. geographical scope) as well as within different EU regions over time (i.e. temporal stability). Findings show that whether DUI or STI modes are more effective in the context of SMEs crucially depends on the timeframe considered, but also the geographical location of SMEs. The study offers novel insights into the diverse and complex nature through which regional innovation evolves over time, advancing understanding on regionalization as well as temporality of SME innovation modes in Europe. It also provides an important basis for discussing innovation policy across Europe.